Chinese Heritage in the Making: Experiences, Negotiations and Contestations - Maags, Christina; Svensson, Marina (Asian Heritages, 2018)
The Chinese state uses cultural heritage as a source of power by linking it to political and economic goals, but heritage discourse has at the same time encouraged new actors to appropriate the discourse to protect their own traditions. This book focuses on that contested nature of heritage, especially through the lens of individuals, local communities, religious groups, and heritage experts. It examines the effect of the internet on heritage-isation, as well as how that process affects different groups of people.